Engrailed homeobox transcription factors as potential markers and targets in cancer. Issue 6 (7th February 2013) - McGrath, Sophie E.; Michael, Agnieszka; Pandha, Hardev; Morgan, Richard
Abstract : Engrailed ( En ) is a member of the homeobox gene family, which encodes a homeodomain‐containing transcription factor that is essential during early development. The only known site of normal adult Engrailed protein (EN) expression is in the nervous system, and it has been implicated in the development of both young‐onset Parkinson's disease as well as autism. Over‐expression of EN has been linked to tumour development in adults, particularly in breast, prostate, melanoma and ovarian cancers, and there is a growing interest in its role as a diagnostic and prognostic biomarker. It is hoped that further work may confirm associations between En expression and therapy‐resistant, poor prognosis cancers, similar to that identified with other homeobox gene profiles. Abstract : ► Engrailed ( En ) is a member of the homeobox gene family. ► En encodes a transcription factor that is essential during early development. ► The only known site of normal adult EN protein expression is in the nervous system. ► Over‐expression of EN has been linked to breast, prostate and ovarian cancers. ► EN2 may prove useful as a biomarker, notably in the urine of prostate cancer patients.